Electoral Rules, Forms of Government and Redistributive Policy: Evidence from Agriculture and Food Policies - Alessandro Olper; Valentina Raimondi (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
We investigate the effect of electoral rules and firms of government on public policy outcomes using a new dataset on agriculture and food policies from 74 countries over the 1960-2005 period. Using both cross-sectional and panel data analyses we find robust evidence that the specific nature of democratic institutions has important consequences for public policy. Proportional democracies and presidential democracies - compared to majoritarian and parliamentary democracies - give more public support to agriculture and less to food consumers. The magnitude of these constitutional effects are stronger for import-competitive sectors and staple food crops. The effects seem independent from the ideology orientation of governments.
Keywords: D72; F13; H23; O13; P16; Q18; 330; Electoral rules; forms of government; agriculture and food policy; political economy.